Pengembangan Aplikasi Penjualan dan Persediaan Barang Berbasis Web Menggunakan Laravel 10 dan Bootstrap 5 untuk Mengoptimalkan Manajemen di Toko Rahmat Jaya - Nuruddhafirah, Ulya; Dewi, Sarini Vita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
Rahmat Jaya Store is a retail business that provides daily necessities but still relies on manual service processes, which are prone to errors, time-consuming, and generate inaccurate reports. This study aims to design and develop a web-based application to support sales processes, inventory management, and customer debt tracking using the Laravel 10 framework and Bootstrap 5. The development follows the waterfall method, starting with requirements analysis through interviews with the store owner and staff, system design using use case diagrams and flowcharts, implementation with the MVC architecture, and testing using black box methods and end-user evaluations. The implementation results show that the system can improve transaction recording efficiency by up to 40%, reduce stock report errors by 70%, and provide more accurate and real-time financial reports. The integrated debt book feature also helps store owners monitor customer receivables systematically and enhances customer satisfaction. Overall, this application demonstrates that web-based information systems can be an effective solution to support the digital transformation of small retail stores by improving operational efficiency, data accuracy, and decision-making. The application is expected to serve as a model for implementing information technology in small-scale retail businesses transitioning from manual to digital systems.